2020
DOI: 10.1021/acsami.0c08285
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Tissue-Adhesive Cryogel Wound Dressing for Rapid Nonpressing Surface Hemorrhage and Wound Repair

Abstract: Cryogels with tissue adhesion have great potential as wound dressings for rapid hemostasis for uncontrollable nonpressing surface hemorrhage and wound healing, but their use has not been reported previously. Herein, we designed a series of antibacterial and antioxidant tissue-adhesive cryogels based on quaternized chitosan (QCS) and polydopamine (PDA). These cryogels had good blood cell and platelet adhesion, enrichment, and activation properties for rapid nonpressing surface hemostasis and wound healing. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
202
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(204 citation statements)
references
References 73 publications
0
202
0
2
Order By: Relevance
“…The in vitro cytotoxicity was evaluated by co-cultivating extract of cryogels and mouse embryonic fibroblast (3 T3) cells. 41 The cryogels with 10 mm diameter and 10 mm in height were immersed in 4 ml Dulbecco's modified eagle medium (DMEM) in a 12 well plate and cultured at 37 C for 24 h to obtain an extract solution. In the meantime, 1 × 10 4 cells were seeded in DMEM with 10% fetal bovine serum (FBS), penicillin sulfate (100 units ml −1 ) and streptomycin (100 μg ml −1 ) and cultured for 24 h at 37 C under a humidified 5% CO 2 .…”
Section: In Vitro Cytotoxicity Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro cytotoxicity was evaluated by co-cultivating extract of cryogels and mouse embryonic fibroblast (3 T3) cells. 41 The cryogels with 10 mm diameter and 10 mm in height were immersed in 4 ml Dulbecco's modified eagle medium (DMEM) in a 12 well plate and cultured at 37 C for 24 h to obtain an extract solution. In the meantime, 1 × 10 4 cells were seeded in DMEM with 10% fetal bovine serum (FBS), penicillin sulfate (100 units ml −1 ) and streptomycin (100 μg ml −1 ) and cultured for 24 h at 37 C under a humidified 5% CO 2 .…”
Section: In Vitro Cytotoxicity Testmentioning
confidence: 99%
“…Recently, many researches have been paid to accomplish hemostasis and defense bacterial invasion simultaneously. [16][17][18][19] In order to improve the antibacterial property of hemostatic materials, antibiotics or silver nanoparticles were usually added to hemostatic materials. Although both of them have well resistance to bacterial invasion, they also possess obvious side effects such as cytotoxicity or drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…4H). Indeed, a large number of studies have demonstrated that, compared to water, blood is more likely to prolong the shape recovery time of hemostats due to its higher viscosity 14,15 . In contrast, there was no signi cant difference in shape recovery time for the MACSs after the absorption of water and blood.…”
Section: Shape-memory Property Of the Macssmentioning
confidence: 99%
“…The pore structure inside the ACS and reported shape-memory hemostats generated by the removal of ice crystals and by gas foaming methods exhibited low interconnectivity, which slowed down the ow speed of the blood. 6,9,10,11,15,16 .…”
Section: Shape-memory Property Of the Macssmentioning
confidence: 99%
See 1 more Smart Citation